British film directors : a critical guide - Shail, Robert (Edinburgh : Edinburgh University Press, 2007)
British national cinema has produced an exceptional track record of innovative, creative and internationally recognised filmmakers, amongst them Alfred Hitchcock, Michael Powell and David Lean. This tradition continues today with the work of directors as diverse as Neil Jordan, Stephen Frears, Mike Leigh and Ken Loach. This concise, authoritative volume analyses critically the work of 100 British directors, from the innovators of the silent period to contemporary auteurs. An introduction places the individual entries in context and examines the role and status of the director within British film production. Balancing academic rigour with accessibility, British Film Directors provides an indispensable reference source for film students at all levels, as well as for the general cinema enthusiast. Key Features A complete list of each director's British feature films. Suggested further reading on each filmmaker. A comprehensive career overview, including biographical information and an assessment of the director's current critical standing. 10 B & W illustrations.
Cover -- Contents -- Acknowledgements -- Illustrations -- Introduction -- How to Use This Guide -- Notes -- British Film Directors -- A -- Birt ACRES -- Lindsay ANDERSON -- Anthony ASQUITH -- Richard (Lord) ATTENBOROUGH -- B -- Roy Ward BAKER -- John BAXTER -- John BOORMAN -- John and Roy BOULTING -- Muriel BOX -- Danny BOYLE -- Kenneth BRANAGH -- Nick BROOMFIELD -- C -- Donald CAMMELL -- Alberto CAVALCANTI -- Gurinder CHADHA -- Alan CLARKE -- Jack CLAYTON -- Jill CRAIGIE -- Charles CRICHTON -- D -- Terence DAVIES -- Basil DEAN -- Basil DEARDEN -- Thorold DICKINSON -- Bill DOUGLAS -- E -- Cy ENDFIELD -- F -- Mike FIGGIS -- Terence FISHER -- Bryan FORBES -- Bill FORSYTH -- Freddie FRANCIS -- Stephen FREARS -- Charles FREND -- Sidney J. FURIE -- G -- Lewis GILBERT -- Terry GILLIAM -- Jack GOLD -- Peter GREENAWAY -- Val GUEST -- H -- John HALAS and Joy BATCHELOR -- Robert HAMER -- Guy HAMILTON -- Cecil HEPWORTH -- Mark HERMAN -- (Sir) Alfred HITCHCOCK -- Mike HODGES -- Hugh HUDSON -- I -- James IVORY -- J -- Derek JARMAN -- Humphrey JENNINGS -- Roland JOFFE -- Neil JORDAN -- Isaac JULIEN -- K -- (Sir) Alexander KORDA -- Zoltan KORDA -- Stanley KUBRICK -- L -- Frank LAUNDER and Sidney GILLIAT -- Philip LEACOCK -- (Sir) David LEAN -- Mike LEIGH -- Richard LESTER -- Ken LOACH -- Joseph LOSEY -- Len LYE -- M -- Alexander MACKENDRICK -- Norman McLAREN -- Shane MEADOWS -- Peter MEDAK -- Anthony MINGHELLA -- N -- Ronald NEAME -- Mike NEWELL -- O -- Laurence (Lord) OLIVIER -- P -- Nick PARK -- (Sir) Alan PARKER -- George PEARSON -- Roman POLANSKI -- Sally POTTER -- Michael POWELL (and Emeric PRESSBURGER) -- R -- Lynne RAMSAY -- (Sir) Carol REED -- Michael REEVES -- Karel REISZ -- Tony RICHARDSON -- Guy RITCHIE -- Bruce ROBINSON -- Nicolas ROEG -- Ken RUSSELL -- S -- Victor SAVILLE -- John SCHLESINGER -- George Albert SMITH -- T -- Pen TENNYSON -- Gerald THOMAS -- Ralph THOMAS -- J. Lee THOMPSON -- Wendy TOYE -- V -- Marcel VARNEL -- W -- Pete WALKER -- Herbert WILCOX -- Michael WINNER -- Michael WINTERBOTTOM -- Y -- Terence YOUNG -- British Feature Film Titles Cited.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Motion picture producers and directors -- Great Britain -- Biography -- Dictionaries; Motion picture producers and directors -- Great Britain -- Biography -- Dictionaries; Producteurs et réalisateurs de cinéma -- Grande-Bretagne -- Biographies -- Dictionnaires anglais; PERFORMING ARTS -- Film & Video -- Direction & Production; BIOGRAPHY & AUTOBIOGRAPHY -- Entertainment & Performing Arts; PERFORMING ARTS -- Film & Video -- Reference; Motion picture producers and directors; Great Britain; Filmregisseur; Regisseur; Großbritannien; Electronic books; dictionaries; Biographies; Dictionaries; Dictionaries; Dictionnaires